PEMBERDAYAAN PEREMPUAN DALAM PENINGKATAN KETERAMPILAN PENGOLAHAN DAN PEMASARAN IKAN DI PULAU HARAPAN KEPULAUAN SERIBU JAKARTA - Ernaningsih, Dwi; Sudarsono, Achmad Budiman; Stefhani, Yosi (Jurnal Abdi Insani, 2024)
The income of the people of Harapan Island is still highly dependent on fishing.  They have not been able to increase their income from fish processing.  The Harapan Island “Red Snapper” Processing and Marketing Group (Polaksar) has problems: (1) Simple fish processing; (2) There is only one processed fish product; (3) Simple product packaging; (4) Limited marketing; (5) Simple business management; (6) Products have not received product certification (SNI) from the Ministry of Marine Affairs and Fisheries. The purpose of the activity is to increase knowledge and skills in processing and marketing processed fish products.  So that fish processing products are more diverse, hygienic, attractive, and use marketing techniques that reach a wider market. The methods used were socialization, training, technology application, mentoring and evaluation. Evaluation was carried out by testing participants' understanding before and after training with a questionnaire followed by statistical tests. Furthermore, the organoleptic test of the resulting product includes aspects of taste, crispness and product color. Mackerel as a raw material for making cheese pilus and fish sticks in fresh conditions based on organoleptic test level obtained a score of 8,2.  The average understanding of the trainees before the training was quite understanding with an average score of 2,81 (quite knowing/understanding) to 4,48 after the training. The two products produced by the 3 groups of participants had an average score for taste of 4, for crispness of 3,9 and color appearance of 4. These scores are good for beginners who have just processed the 2 products.  Product packaging and logos were made more attractive and trainees used Instagram as a promotional medium. Overall, the trainees were able to make the products according to the trainer's directions, in a short time the processed results were quite good.